Marketing products and services in the dynamic environment. - Chan, Cindy Li Xia. (2011)
Companies today are overtly aware that they can add a little more green to their wallets by putting a little more green in their portfolios. In its endeavour to enjoy a slice of this burgeoning profit pie, Quirky, the retail of Ark Industries, has enlisted the team to recommend strategies that can boost the performance of its green apparel segment.